Taxonomy of the genus Cyrtopholis Simon, 1892 (Araneae, Mygalomorphae, Theraphosidae): Cuban species described by Pelegrin Franganillo Balboa - Fabiano-Da-Silva, Willian; Leite Guadanucci, Jose Paulo [UNESP]; Garcia, Giraldo Alayon; Lucas, Sylvia Marlene; Dasilva, Marcio Bernardino (Magnolia Press, 2020)
Cyrtopholis Simon 1892 is a spider genus from the Caribbean islands characterized by the presence of stridulatory setae on trochanter of palps and legs I. Franganillo Balboa described eight species of Cyrtopholis Simon 1892 from Cuba between 1926-1936. The type-material is deposited in the Instituto de Ecologia y Sistematica do Ministerio de Ciencias, Tecnologia e Meio Ambiente, La Habana, Cuba. Four species are redescribed here: Cvrtopholis plumosa Franganillo, 1931, Cyrtopholis major Franganillo. 1926, Cyrtopholis unispina Franganillo, 1926 and Cyrtopholis gibbosa Franganillo, 1936. Cvrtopholis ischnoculoformis Franganillo, 1926 is based on a juvenile specimen without stridulatory setae, and it is therefore considered here as species inquirenda. The type-material of two other species were not located: Cyrtopholis anacanta Franganillo, 1935 and Cyrtopholis obsoleta (Franganillo, 1935), and are considered to be lost. These two species are here considered as species inquirenda, since the original descriptions do not permit identification. Cyrtopholis respina Franganillo 1935 is considered a nomen dubium, due to the lack of a formal description and a doubtful citation.
Keywords: Caribbean species; taxonomy; Theraphosinae